Adult attachment, stress, and romantic relationships. (February 2017) - Simpson, Jeffry A; Rholes, W Steven
Highlights: Describes how anxiously and avoidantly attached people think, feel, and behave when distressed. Reviews key principles of attachment theory. Indicates how attachment anxiety and avoidance are associated with different patterns of emotion regulation. Presents a diathesis-stress model that describes these processes in anxiously and avoidantly attached people. Abstract : In this article, we discuss theory and research on how individuals who have insecure adult romantic attachment orientations typically think, feel, and behave when they or their romantic partners encounter certain types of chronic or acute stress. We first review basic principles of attachment theory and then discuss how two forms of attachment insecurity — anxiety and avoidance — are associated with unique patterns of emotion regulation in response to certain types of threatening/distressing situations. We then discuss a Diathesis-Stress Process Model that has guided our research, highlighting studies that provide support for certain pathways of the model.